The Role of Religion in Enforcement of Environmental Law in Indonesia - Muhammad Nur Fadilah Syahraya (Universitas Muhammadiyah Surakarta, 2024)
The environment is something that is the main basis and foundation of life. If the residents in an ecology can maintain and preserve the ecology in that area, then peace will soon be achieved and balance will remain stable. So from this there is what is called human awareness as one of the owners of instruments which are quite important but have equal degrees. Many legal products are for the environment, but many also fail in them. The role of religion is very much needed in fostering a sense of human awareness of the environment so as to create a balanced and beautiful environment.